From Insurgency to Bureaucracy: Free Aceh Movement, Aceh Party and the New Face of Conflict - Mohammad Hasan Ansori (Stability : International Journal of Security and Development, 2012)
The settling of the 32-year Aceh conflict not only transformed former members of the Free Aceh Movement (GAM) into administrators, constructing a new circle of elites, but also created opportunities and new spaces for economic and socio-political competition and contestation. Hence, this transformation sowed the seeds of an emerging conflict in Aceh. This study investigates the emerging conflict patterns along with their causes and the actors involved. Three patterns of conflict have been identified as having emerged during the post-Helsinki Peace Agreement period: (i) a conflict among the former GAM elites, (ii) a conflict between the former GAM elites and the former GAM rank-and-file combatants, and (iii) a conflict between the ethnic Acehnese majority and the diverse ethnic minority groups. While the first and second conflicts are primarily induced by individual self-interest, the third is specifically triggered by the social and political discrimination as well as by under-development.